Low fertility in Austria and the Czech Republic: Gradual policy adjustments - Tomáš Sobotka (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
This article provides a comparative analysis of fertility and family transformations and policy responses in Austria and the Czech Republic, two neighbouring countries in Central Europe that were until 1989 separated by the "Iron Curtain" that divided two competing political blocs in Europe. Such comparison is partly stimulated by the geographic proximity, shared history and culture of these two countries in the past and their gradual economic and social convergence in the last quarter of century. During this period both societies also grew surprisingly similar in their fertility and family patterns and main family policy trends. Fertility in both countries is relatively low, but not extremely low when compared with the countries of Southern Europe or East Asia, with the period total fertility rate recently converging to 1.45 and cohort fertility rates of the women born in the mid-1970s projected at 1.65 (Austria) and 1.8 children per woman (Czech Republic). Austrian fertility rates have been remarkably stable since the 1980s, while in the Czech Republic fertility had imploded during the 1990s, following the political regime change, before it started recovering in the 2000s. In both countries childbearing has rapidly shifted to later ages and increasingly has taken place outside marriage, with over a half of first births now born to cohabiting couples and single mothers. Czech women retain considerably lower childlessness, possibly due to the persistently strong normative support to parenthood in the country. Family policies, relatively generous in terms of government expenditures, were until recently dominated by a view that mothers should stay at home for an extended period with their children, making the return to employment difficult for women. However, recent policy adjustments in both countries have expanded the range of options available to parents, making the parental leave more flexible and, in the case of Austria, gradually expanding public childcare and supporting a stronger involvement of men in childrearing.
Keywords: 300; Fertility; low fertility; family; family policies; Czech Republic; Austria